Calculation Substantiation of the Optimal Anchoring Length of the Working Reinforcement of Precast-Monolithic Piles in the Cryolithozone - Mestnikov, V V; Mestnikova, I V (IOP conference series. Materials Science and Engineering, 2021)
The subject of research is the development of rational types of foundations in permafrost. These article is proposed use of prefabricated monolithic piles, providing for a combination of drilling and bored methods of pile foundations. The computational substantiation of the anchoring length of the working reinforcement of precast-monolithic piles under the influence of tangential forces of frost heaving has been carried out. Mathematical modeling of the joint between the prefabricated part of the pile and the monolithic part was carried out in the Ansys software.